Interprofessional education and practice guide No. 10: Developing, supporting and sustaining a team of facilitators in online interprofessional education. Issue 1 (2nd January 2020) - Evans, Sherryn; Ward, Catherine; Shaw, Nicole; Walker, Arlene; Knight, Tess; Sutherland-Smith, Wendy
ABSTRACT: Whilst we have seen a growth in the use of information and communication technologies to deliver interprofessional education (IPE) in the last decade, little has been written about facilitating IPE in the online environment. For the last 10 years, the Faculty of Health at Deakin University has offered a fully online IPE course that has consistently employed facilitators to guide interprofessional teams in both asynchronous and synchronous (real-time) online interprofessional learning experiences. This Interprofessional Education and Practice Guide draws on the Deakin University leadership experience in supporting teams of online IPE facilitators over the last decade, underpinned by prior research and key literature. The key lessons provided in this guide aim to assist others in developing, supporting and sustaining a team of online IPE facilitators to guide asynchronous and synchronous online interprofessional learning experiences.